2017
DOI: 10.1007/s00784-017-2079-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caries and dental fluorosis on oral health-related quality of life: a cross-sectional study in schoolchildren receiving water naturally fluoridated at above-optimal levels

Abstract: Deterioration on OHRQoL found in children as a sequel of caries and fluorosis should be considered when designing health policies leading to prevention and effective health promotion programs and incorporated to clinical guidelines for timely dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 41 publications
(43 reference statements)
3
55
2
3
Order By: Relevance
“…Studies that have evaluated the relationship between DED and OHRQoL have shown a greater impact in children with more severe hypoplasia and diffuse opacities . Despite the clinical complexity of MIH, studies that have evaluated the impact of this change on OHRQoL are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have evaluated the relationship between DED and OHRQoL have shown a greater impact in children with more severe hypoplasia and diffuse opacities . Despite the clinical complexity of MIH, studies that have evaluated the impact of this change on OHRQoL are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Studies differed in their grouping of caries scores. For example, nine different caries surfaces measures and seven caries teeth measures were identified in this review. Some studies grouped them to classify caries as dentin and enamel lesions while others classified them as initial/early, moderate/established and severe/extensive lesions .…”
Section: Discussionmentioning
confidence: 99%
“…A cárie é uma doença multifatorial, que não se limita apenas a alteração da estrutura dental (14) caries (International Caries Detection and Assessment System, ICDAS II). Essa doença causa sintomatologia dolorosa e alterações na linguagem oral (15) missing, and filled teeth--D-DMFT in permanent teeth or d-dfmt in primary teeth, assim como impacta a qualidade de vida e a percepção estética, devido aos sinais e sintomas apresentados, como observado no presente estudo.…”
Section: Discussionunclassified
“…A literatura aponta que, quando utilizados em conjunto, podem beneficiar o planejamento de serviços odontológicos, uma vez que os achados clínicos sozinhos geralmente superestimam as necessidades do paciente (14) . Além disso, os indicadores sócio-odontológicos podem ser usados para priorizar o tratamento odontológico em situações de falta de recursos.…”
Section: Discussionunclassified
See 1 more Smart Citation